Existing bitter medicines for fighting 2019‐nCoV‐associated infectious diseases. Issue 5 (13th April 2020) - Li, Xiangqi; Zhang, Chaobao; Liu, Lianyong; Gu, Mingjun
Abstract: The sudden outbreak of COVID‐19 has led to more than seven thousand deaths. Unfortunately, there are no specific drugs available to cure this disease. Type 2 taste receptors (TAS2Rs) may play an important role in host defense mechanisms. Based on the idea of host‐directed therapy (HDT), we performed a negative co‐expression analysis using big data of 60 000 Affymetrix expression arrays and 5000 TCGA data sets to determine the functions of TAS2R10, which can be activated by numerous bitter substances. Excitingly, we found that the main functions of TAS2R10 involved controlling infectious diseases caused by bacteria, viruses, and parasites, suggesting that TAS2R10 is a key trigger of host defense pathways. To quickly guide the clinical treatment of 2019‐nCoV, we searched currently available drugs that are agonists of TAS2Rs. We identified many cheap, available, and safe medicines, such as diphenidol, quinine, chloroquine, artemisinin, chlorpheniramine, yohimbine, and dextromethorphan, which may target the most common symptoms caused by 2019‐nCoV. We suggest that a cocktail‐like recipe of existing bitter drugs may help doctors to fight this catastrophic disease and that the general public may drink or eat bitter substances, such as coffee, tea, or bitter vegetables, to reduce the risk of infection.